Concerto for 4 violins, strings and basso continuo fur 4 violinen, streicher und basso continuo D mayor/D-dur/Re majeur Op.3/1 (P 146). No.1258 - VIVALDI, Antonio (Ernst Eulenburg)
I. Allegro.n2. Largo e Spiccato.n3. Allegro